A construção da identidade da criança na Educação Infantil: reflexões sobre cultura de pares e relações étnico-raciais - Silva, Ana Carolina de Melo (Universidade Federal de São Carlos, 2023)
The present research, of a qualitative and bibliographic nature, aims to analyze and understand the studies about the construction of the child's identity in the educational field, seeking an answer to the following problem question: How does the construction of the child's identity in Early Childhood Education happen through interactions with other children (between peers) and with adults? The work also seeks to answer a question arising from the main one, which is: how does the construction of the child's identity take place in the face of ethnic and cultural diversity? The research verified the importance of the relationship with the other in the construction of identity and in the recognition of subjectivities, since it is a complex and multifaceted process, of gradual construction and that takes place through interactions and the development of autonomy. The teacher plays a fundamental role in this construction by moving away from adult-centrism and understanding that children produce culture, not as an imitation of the world of adults, but as agents and co-responsible for their own development. For this, it is necessary that pedagogical practices are based on the construction of an anti-racist education, focusing on representativeness, identification and recognition of blackness and on self-esteem work, on combating racism and on valuing children as protagonists of their own stories.
The construction of the child's identity in Early Childhood Education reflections on peer culture and ethnic-racial relations
Keywords: Identidade; Identity; Educação Infantil; Early Childhood Education; Relações Étnico-raciais; Ethnic-racial Relations; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO